A theoretical model for rehabilitation counseling - Hershenson, David B. [Verfasser] (My University, 1990)
"Both logically (as tertiary prevention) and politically (as a separate profession) rehabilitation counseling needs a theory base that is distinct from curative models. A model is proposed that identifies four elements contributing to coping that can be disrupted by disability and the type of intervention that each affected element may require: (a) restoring or replacing assets and skills, (b) reintegrating the self-image, (c) reformulating goals, and (d) restructuring the environment. Consequently, the functions of the rehabilitation counselor are: coordination (for a), counseling (for b and c), and consultation (for d)." (author's abstract) ((en)) In dem Beitrag wird ein theoretisches Modell für die Rehabilitationsberatung vorgeschlagen, dessen Elemente darauf abzielen, die Fähigkeiten und Kenntnisse eines Behinderten wieder herzustellen oder zu ersetzen, sein Selbstbewusstsein wieder aufzubauen, neue Ziele zu formulieren und die Umgebung anzupassen. Daraus folgt, dass der Rehabilitationsberater die Aufgaben der Koordination, der Beratung und der Rücksprache hat. (IAB)
Theoriemodell für die Rehabilitationsberatung
Keywords: L 5.2 Berufsintegrationsplanung; L 5 Beratung & Orientierung; Rehabilitationsberatung; Beratungskonzept